(untitled) (Journal of Geography and Environmental Management, 2018)
Agritourism is associated with modern expansion kinds of tourism, which are popular in many countries of the World. Opportunities for its development in Kazakhstan haven’t absolutely clear which makes researches in this direction very urgent. A brief description of the administrative districts according to the potential for the agritourism development are presented. The results of opportunities assessment for development and territorial organization of agritourism based on crop production and livestock sector are shown. All opportunities according to the following areas are grouped: households and business sector. For study of business sector the following criteria are recommended: profitability or unprofitability of enterprises; support of employment for rural population; the quality of work places; links with local base of resources; refinement of the agritourism enterprises in local economy structure; spatial integration of local community. It is noted that the economy and business spheres of Karaganda region’s are not ready for agritourism development. Factual materials that confirm this conclusion are presented.